2011
DOI: 10.1007/s13311-011-0035-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic Treatment for Acute Spinal Cord Injury

Abstract: Summary: Spinal cord injury (SCI) is a devastating condition that affects approximately 11,000 patients each year in the United States. Although a significant amount of research has been conducted to clarify the pathophysiology of SCI, there are limited therapeutic interventions that are currently available in the clinic. Moderate hypothermia has been used in a variety of experimental and clinical situations to target several neurological disorders, including traumatic brain and SCI. Recent studies using clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 94 publications
0
43
0
2
Order By: Relevance
“…10 Dietrich et al 11 recently reviewed hypothermia as a protective strategy, noting the demonstrated advantages of hypothermia while pointing out the complexities imposed by Note:-Temp indicates temperature; R, room temperature PL infusion; I, PL cooled in a refrigerator before infusion (temperature approximately 3°C); IB, cooled PL passed through extension tubing coiled in an IB immediately prior to entering the microcatheter. This step was added to correct for any warming that occurred between the hanging bag and the microcatheter as the fluid passed via the pump.…”
Section: Discussionmentioning
confidence: 99%
“…10 Dietrich et al 11 recently reviewed hypothermia as a protective strategy, noting the demonstrated advantages of hypothermia while pointing out the complexities imposed by Note:-Temp indicates temperature; R, room temperature PL infusion; I, PL cooled in a refrigerator before infusion (temperature approximately 3°C); IB, cooled PL passed through extension tubing coiled in an IB immediately prior to entering the microcatheter. This step was added to correct for any warming that occurred between the hanging bag and the microcatheter as the fluid passed via the pump.…”
Section: Discussionmentioning
confidence: 99%
“…As technology improved and our understanding of the possible beneficial effects of systemic hypothermia grew, so did interest in applying this strategy to the acute spinal cord injury patient (9,10). Multiple animal studies have suggested a positive effect of either locally or systemically applied therapeutic hypothermia (9).…”
Section: Therapeutic Hypothermia For Acute Spinal Cord Injurymentioning
confidence: 99%
“…H ypothermia for treatment of patients with spinal cord injury (SCI) shows great promise as an acute neuroprotective therapy (Dietrich et al, 2009(Dietrich et al, , 2011Dietrich, 2012;Maybhate et al, 2012;Silasi et al, 2012). In addition to SCI, hypothermia has been shown to lead to functional improvements in many other injury types, including cardiac arrest (Arrich, 2007;Madhok et al, 2010;Beddingfield and Clark, 2012), stroke (Groysman et al, 2011;Chang and Marshall, 2012;Lakhan and Pamplona, 2012), ischemiareperfusion injury (Kawamura et al, 2006), traumatic brain injury (Tomura et al, 2012), and coma (Bouwes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%